2015
DOI: 10.4142/jvs.2015.16.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Intrapancreatic ectopic splenic tissue found in a cloned miniature pig

Abstract: Somatic cell nuclear transfer (SCNT) is a cost-effective technique for producing transgenic pigs. However, abnormalities in the cloned pigs might prevent use these animals for clinical applications or disease modeling. In the present study, we generated several cloned pigs. One of the pigs was found to have intrapancreatic ectopic splenic tissue during histopathology analysis although this animal was grossly normal and genetically identical to the other cloned pigs. Ectopic splenic tissue in the pancreas is ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…On the other hand, the presence of a fibrous capsule partially separating the adjacent pancreatic parenchyma from the accessory spleen was observed a few of the animals studied (2/8 cases). A fibrotic capsule surrounding accessory spleens has also been observed in previous studies in minipigs ( 9 ) and other animals ( 8 , 16 ), suggesting that capsule formation is not related to the animal species. Regarding the presence of trabeculae, it should be noted that all wild boars in the study with confirmed presence of IPAS had trabecular connective tissue.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, the presence of a fibrous capsule partially separating the adjacent pancreatic parenchyma from the accessory spleen was observed a few of the animals studied (2/8 cases). A fibrotic capsule surrounding accessory spleens has also been observed in previous studies in minipigs ( 9 ) and other animals ( 8 , 16 ), suggesting that capsule formation is not related to the animal species. Regarding the presence of trabeculae, it should be noted that all wild boars in the study with confirmed presence of IPAS had trabecular connective tissue.…”
Section: Discussionsupporting
confidence: 72%
“…The description of intrapancreatic accessory spleen (IPAS) is a frequent phenomenon in humans that poses no clinical significance (4,6). However, the occurrence of IPASs in animals is poorly documented in the literature, with only a few cases described in dogs and cats (5,7,8), domestic pigs (9,10), rabbits (3,(11)(12)(13), marine mammals (14)(15)(16)(17) and non-human primates (18).…”
Section: Introductionmentioning
confidence: 99%
“…3 Ectopic spleen has been recorded in the pancreas of a cloned Yucatan minipig, and accessory spleens may be found in the gastrosplenic ligament. 4 As the parathyroid is often found embedded in the cervical thymus, it is not considered an ectopic tissue in this location.…”
Section: Chapter 2 Systemic Pathologymentioning
confidence: 99%
“…Intrapancreatic splenic tissue (IPST) is sporadically reported in veterinary species, including dogs, 1 cats, 1,2 rabbits, 3,4 pigs, 5,6 cetaceans 7 and non-human primates. 8,9 IPST can have two possible origins, indistinguishable on histopathology: splenosis, which consists in autotransplantation of splenic tissue in a patient (ie, following trauma); or accessory spleen, which consists of aberrantly located splenic masses of congenital origin.…”
Section: Introductionmentioning
confidence: 99%